Development of hydration strategies to optimize performance for athletes in high-intensity sports and in sports with repeated intense efforts - Maughan, R. J.; Shirreffs, S. M. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Hypohydration - if sufficiently severe - adversely affects athletic performance and poses a risk to health. Strength and power events are generally less affected than endurance events, but performance in team sports that involve repeated intense efforts will be impaired. Mild hypohydration is not harmful, but many athletes begin exercise already hypohydrated. Athletes are encouraged to begin exercise well hydrated and - where opportunities exist - to consume fluid during exercise to limit water and salt deficits. In high-intensity efforts, there is no need, and may be no opportunity, to drink during competition. Most team sports players do not drink enough to match sweat losses, but some drink too much and a few may develop hyponatremia because of excessive fluid intake. Athletes should assess their hydration status and develop a personalized hydration strategy that takes account of exercise, environment and individual needs. Pre-exercise hydration status can be assessed from urine markers. Short-term changes in hydration can be estimated from the change in body mass. Sweat salt losses can be determined by collection and analysis of sweat samples. An appropriate drinking strategy will take account of pre-exercise hydration status and of fluid, electrolyte and substrate needs before, during and after exercise.